Metal–Organic Frameworks and Metal–Organic Gels for Oxygen Electrocatalysis: Structural and Compositional Considerations - Wang, Hao; Chen, Biao‐Hua; Liu, Di‐Jia (Advanced materials (Weinheim), 2021)
Increasing demand for sustainable and clean energy is calling for the next‐generation energy conversion and storage technologies such as fuel cells, water electrolyzers, CO2/N2 reduction electrolyzers, metal–air batteries, etc. All these electrochemical processes involve oxygen electrocatalysis. Boosting the intrinsic activity and the active‐site density through rational design of metal–organic frameworks (MOFs) and metal–organic gels (MOGs) as precursors represents a new approach toward improving oxygen electrocatalysis efficiency. MOFs/MOGs afford a broad selection of combinations between metal nodes and organic linkers and are known to produce electrocatalysts with high surface areas, variable porosity, and excellent activity after pyrolysis. Some recent studies on MOFs/MOGs for oxygen electrocatalysis and their new perspectives in synthesis, characterization, and performance are discussed. New insights on the structural and compositional design in MOF/MOG‐derived oxygen electrocatalysts are summarized. Critical challenges and future research directions are also outlined. Boosting the intrinsic activity and the active‐site density through rational design of metal–organic frameworks (MOFs) and metal–organic gels (MOGs) as precursors represents a new approach of improving oxygen electrocatalysis efficiency. Several key compositional and structural considerations for the MOF/MOG design and new perspectives between synthesis, characterization, and performance are comprehensively discussed.